Determinants of last lap speed in paced and maximal 1500-m time trials - Bellinger, P.; Derave, W.; Lievens, E.; Kennedy, B.; Arnold, B.; Rice, H.; Minahan, C. (European Journal of Applied Physiology, 2021)
Purpose: The present study identified the physiological and performance characteristics that are deterministic during a maximal 1500-m time trial and in paced 1500-m time trials, with an all-out last lap. Methods: Thirty-two trained middle-distance runners (n = 21 male, VO2peak: 72.1 ± 3.2; n = 11, female, VO2peak: 61.2 ± 3.7 mL kg-1 min-1) completed a 1500-m time trial in the fastest time possible (1500FAST) as well as a 1500MOD and 1500SLOW trial whereby mean speed was reduced during the 0-1100 m by 5% and 10%, respectively. Anaerobic speed reserve (ASR), running economy (RE), the velocity corresponding with VO2peak (VVO2peak), maximal sprint speed (MSS) and maximal accumulated oxygen deficit (MAOD) were determined during additional testing. Carnosine content was quantified by proton magnetic resonance spectroscopy in the gastrocnemius and expressed as a Z-score to estimate muscle fibre typology. Results: 1500FAST time was best explained by RE and VVO2peak in female runners (adjusted r2 = 0.80, P < 0.001), in addition to the 0-1100-m speed relative to VVO2peak in male runners (adjusted r2 = 0.72, P < 0.001). Runners with a higher gastrocnemius carnosine Z-score (i.e., higher estimated percentage of type II fibres) and greater MAOD, reduced their last lap time to a greater extent in the paced 1500-m trials. Neither ASR nor MSS was associated with last lap time in the paced trials. Conclusion: These findings suggest that VVO2 peak and RE are key determinants of 1500-m running performance with a sustained pace from the start, while a higher carnosine Z-score and MAOD are more important for last lap speed in tactical 1500-m races.